Antibiotic-Drug Interactions in the Intensive Care Unit: A Literature Review - Paweł Radkowski; Maria Derkaczew; Michał Mazuchowski; Annas Moussa; Katarzyna Podhorodecka; Justyna Dawidowska-Fidrych; Małgorzata Braczkowska-Skibińska; Daria Synia; Karol Śliwa; Marta Wiszpolska; Marta Majewska (MDPI AG, 2024)
Interactions between drugs are a common problem in Intensive Care Unit patients, as they mainly have a critical condition that often demands the administration of multiple drugs simultaneously. Antibiotics are among the most frequently used medications, as infectious diseases are often observed in ICU patients. In this review, the most important antibiotic-drug interactions, based on the pharmacokinetic and pharmacodynamic mechanisms, were gathered together and described. In particular, some of the most important interactions with main groups of antibacterial drugs were observed in patients simultaneously prescribed oral anticoagulants, NSAIDs, loop diuretics, and valproic acid. As a result, the activity of drugs can be increased or decreased, as dosage modification might be necessary. It should be noted that these crucial interactions can help predict and avoid negative consequences, leading to better patient recovery. Moreover, since there are other factors, such as fluid therapy or albumins, which may also modify the effectiveness of antibacterial therapy, it is important for anaesthesiologists to be aware of them.